Pengaruh Model Pembelajaran Creative Problem Solving (CPS) Berbantuan LKPD terhadap Kemampuan Pemecahan Masalah dalam Pembelajaran IPA SMP - Aulia Salsabila; Rusdianto Rusdianto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Problem-solving skills are an important competency in science learning, but at the junior high school level it is still relatively low, because the learning process has not fully involved students actively. This condition requires the application of a learning model that is able to encourage student involvement and train thinking skills systematically. This study aims to analyze the effect of the application of the Creative Problem Solving (CPS) learning model assisted by Student Worksheets (LKPD) on the problem-solving ability of junior high school students in science learning. The study used the quasy experiment method with a posttest-only control group design. The subject of the study was grade VII students of SMPN 2 Maesan, Bondowoso, East Java, who were selected using the purposive sampling technique. The research instrument is in the form of a description test that is prepared based on indicators of problem-solving ability which includes understanding problems, planning solutions, implementing plans, and re-checking. Data were analyzed using inferential statistical analysis. The results showed that the average problem-solving ability of students in the experimental class was in the high category, while the control class was in the medium category. The results of the analysis showed a significant difference between the two classes. Thus, it can be concluded that the application of the Creative Problem Solving (CPS) model assisted by Student Worksheets (LKPD) has a significant effect on students' problem-solving ability in science learning.